Students' Perceptions of WordUp Utilization in Vocabulary Learning - Gilang Hizbullah; Rahmah Fithriani (IJECA (International Journal of Education and Curriculum Application), 2025)
Given the increasing role of mobile technology in language education, understanding students’ perceptions of gamified vocabulary applications is essential for optimizing their effectiveness in EFL contexts. This study aims to explore junior high school students’ perceptions of the WordUp application as a digital tool for enhancing vocabulary mastery and to identify its contributions to the field of mobile-assisted language learning. Employing a phenomenological approach, the research involved observations, semi-structured interviews, and documentation with 12 students from an Islamic junior high school in Sumatra, Indonesia, and the data were analyzed by thematic analysis. The findings indicate that students generally reported positive experiences, including engaging and enjoyable learning activities, gamified vocabulary practice that fosters intrinsic motivation among teenagers, authentic multimodal contexts that support comprehension, and noticeable improvement in vocabulary mastery. Nevertheless, several challenges emerged, such as information overload, which sometimes hindered retention, and limited content coverage that did not always align with students’ immediate learning needs. The study underscores the significant role of mobile applications in facilitating language learning and offers practical recommendations for improving the user experience of WordUp to better accommodate learners’ preferences. By providing empirical insights into students’ experiences, this research contributes to the understanding of how gamified mobile applications can be optimized to enhance vocabulary acquisition in English as a foreign language contexts.This study investigates junior high school students' perceptions of the WordUp application as a tool for enhancing vocabulary mastery. The research employed a phenomenological approach, involving observations, semi-structured interviews, and documentation with 12 students from an Islamic junior high school in Sumatra, Indonesia. The findings revealed that students generally had positive experiences such us fun learning, gamified vocabulary learning that triggers instrinsic motivation in teen learners, authentic multimodal context and improved vocabulary. However, challenges such as overload information and limitations in content. The study highlighted the importance of mobile applications in language learning and provides recommendations for enhancing the user experience of WordUp to better meet students' needs.